Upaya Meningkatkan Hasil Belajar Materi IPS Indahnya Kebersamaan melalui Metode Diskusi Siswa Kelas IV SD Negeri 44 Mataram - Istianatin, Baiq (Lembaga Yasin AlSys, 2022)
The purpose of this study was to determine the increase in learning outcomes of social studies material The Beauty of Togetherness through the Discussion Method for Class IV students of SD Negeri 44 Mataram in the Academic Year of 2021/2022. This research is a classroom action research. The subjects in this study were 28 fourth grade students at SD Negeri 44 Mataram with 10 male students and 18 female students. Data collection techniques used are observation, documentation, and tests. Observation is used to collect data on interest in learning. The test is used to measure learning achievement in Mathematics. The data analysis used is descriptive qualitative and descriptive quantitative. The results showed that: 1) The data on student learning outcomes in the Social Sciences material The Beauty of Togetherness using discussion mode increased from the initial data obtained classical completeness was 57.14%, increased to 67.86% in the first cycle, to 82.14% in the second cycle. to 100% in cycle III. So student learning outcomes in social studies material The Beauty of Togetherness using the discussion method carried out by the teacher is very good; 2) Teaching and learning activities carried out by teachers have increased from a score of 26 (72.23%) in cycle I, to 29 (80.56) in cycle II, to 32 (88.89) in cycle III; 3) Student learning activities, it can be described that the average percentage in the first cycle is 66.67%. However, in the second cycle, student learning activities increased to 77.78% in the third cycle, and to 86.11%. So the student learning activities in the Social Sciences material The Beauty of Togetherness is good.